Factors Affecting Malaysia–China Construction Joint Venture Projects - Mo , Xuan (2012)

(untitled)
With the world’s economic globalization growing at a rapid pace over the past years, the international joint ventures (IJVs) have been popular increasingly in a large number of countries, as well as many industries. For the purposes of sharing risk, complementing or integrating resources, authority regulatory etc., the IJVs have been widely utilized as a competitive form by the multinational enterprises and other organization entering into global cooperation. Therefore IJV has long been drawing attention by so many scholars, a few of whom found that more than half of the past IJVs performed unsatisfactorily or poorly, even failed.